Contribution of Adsorption Phenomena to the Degradation Study of Marble Statues in the Archaeological Museum of Philippi, Greece - Vithleem Floropoulou; Triantafyllia Agelakopoulou; Eleni Metaxa; Chaido-Stefania Karagianni; Fani Roubani-Kalantzopoulou (Adsorption Science & Technology)
A description is provided of the contribution of time-resolved analysis in understanding adsorption phenomena and its contribution to an examination of the overall degradation mechanism of authentic marble pieces brought about by air pollution. As a consequence, a scientific answer has been provided to the question “how are materials of cultural heritage affected by air pollution?” The use of reversed-flow inverse gas chromatography (RF-IGC) has allowed the determination of important local physicochemical quantities relating to the influence of three light hydrocarbons, either in the presence or absence of sulphur dioxide. A detailed analysis of the results as well as a correlation study is given.